Pengaruh Digital Marketing Terhadap Niat Berkunjung Wisatawan Ke Destinasi Wisata Kecamatan Balige (Satu Study Pada Dinas Kebudayaan Dan Pariwisata Kabupaten Toba) - Rio S. Siagian; Charles Makmur Sainturi; Kepler Sinaga (Research and Community Service UNIVERSITAS KALBIS, 2026)
This study aims to analyze and explain the effect of digital marketing on tourists' intention to visit tourist destinations in Balige District, Toba Regency. The independent variables in this study include content quality, engagement, ease of access to information, and electronic word of mouth (e-WOM), while the dependent variable is tourists' intention to visit. The study uses a quantitative approach with a survey method. Data collection was conducted by distributing questionnaires to 96 respondents who were tourists or potential tourists who obtained information about Balige tourist destinations through digital media. The data analysis techniques used included validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-tests), simultaneous tests (F-tests), and coefficient of determination tests (R²). The results showed that, partially, content quality, engagement, ease of access to information, and e-WOM had a positive and significant effect on tourists' intention to visit. Simultaneously, the four digital marketing variables were also proven to have a significant effect on tourists' intention to visit the Balige District tourist destination. The coefficient of determination value shows that digital marketing variables are able to explain most of the variation in tourist visitation intent, while the rest is influenced by other factors outside the research model. These findings confirm that optimizing digital marketing strategies through the presentation of informative and credible content, increasing audience interaction and engagement, ease of access to information, and strengthening positive reviews in digital media are strategic factors in increasing tourist visitation intent.